GROWTH RATE OF BLOOD COCKLE (Anadara granosa) SPAT IN INTERTIDAL ZONE PANIPAHAN ROKAN HILIR DISTRICT RIAU PROVINCE - Zaryano, Andre Febriadi; Nasution, Syafruddin; ', Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in November 2015 to January 2016 in Coastal Panipahan Rokan Hilir Riau Province, aimed to compare the growth rate of blood cockle spat (A. granosa) on the three different part of intertidal zone. The method used in this study is an experimental method by using a completely randomized design (CRD) of the factors with 3 levels of treatment, each treatment using 3 replications. The treatments used in the maintenance of blood clam spat that is treatment IBA (upper intertidal zone), treatment IBT (middle intertidal zone), and treatment IBB (lower intertidal zone). The fence netting used measuring 50 × 50 cm as many 9 units are arranged randomly. Blood cockle spat are stocked as many as 100 individuals / fence netting. The results showed that the average rate of growth of the blood cockle spat indicate that lower intertidal zone to produce a faster growth rate than the middle intertidal zone and upper intertidal zone.Keyword: Growth Rate, Anadara granosa, Intertidal Zone, Panipahan